Preliminary evaluation of dental hygiene curriculum: Assessment and management of peri‐implant conditions and diseases. Issue 6 (9th March 2020) - Arnett, Michelle C.; Reibel, Yvette G.; Evans, Michael D.; Stull, Cynthia L.
Abstract: Objective: The purpose of this study was to investigate dental hygiene (DH) educational programs' didactic and clinical curriculum in the management of peri‐implant diseases and conditions. The specific aims were (1) assess if evidence‐based content for peri‐implant diseases and conditions are currently included in didactic and clinical DH curriculum and (2) determine if DH education programs are currently preparing students at a level of clinical competency for the assessment and management of peri‐implant diseases and conditions. Design: A cross‐sectional study of DH faculty member(s) from 331 United States entry‐level programs responsible for didactic and clinical curriculum for peri‐implant diseases and conditions were surveyed. The survey was disseminated electronically via Qualtrics xm August 2019 for a response rate of 26%. Results: The results showed didactic courses taught DH students the etiology of peri‐mucositis and peri‐implantitis (98%), clinical characteristics (98%), and risk factors contributing to these implant diseases (96%). Evaluation methods to determine student level of competency in a didactic setting included quizzes/examinations (98%), case‐based examinations (63%), and written essays (6%). Eighty‐five percent reported DH students are not required in a clinical setting to provide care for patients with peri‐implant diseases and conditions. Conclusions: Study results suggest DH education programs may need to revise didactic and clinical curriculum to ensure students graduate at a level of clinical competency for assessing and managing peri‐implant conditions and diseases. DH educational programs should consider requiring clinical patient experiences for the assessment and management of peri‐mucositis and peri‐implantitis to prepare students for their professional role.